Constitutionalism and Enlightenment in the Havana liberal press (1810–1814) (Islas, 2023)
Introduction: This study assesses the ideological effects that arose from the emergence of political press in Havana following the enactment of the decree on freedom of the press approved by the Spanish Cortes on November 10, 1810.Methods: The study employed bibliographic review, document analysis, historical methods, and source criticism to provide a contextualized evaluation of the described phenomenon.Results: Upon concluding the investigation, it can be affirmed that the enforcement of the decree on freedom of the press of November 10, 1810 in Havana legitimized the existence of a politically influential press, despite the brief validity of the aforementioned legal order.Conclusions: The emergence of political press in Havana contributed to the dissemination of enlightened ideas of constitutionalism, created space for political-public debates, and laid the foundation for the formation of public opinion among the educated circles of society.
Keywords: constitutionalism; Enlightenment; Cuba; liberalism